Hydrocracking of n-C16 over MFI Zeolite Nano-sheets - Effect of the Si/Al Ratio - Parker, Mohamed Habeeb (Department of Chemical Engineering, 2019)
The combination of MFI zeolite nano-sheets with competitive adsorption of water (H2O) in hydrocracking of long-chain paraffins presents a promising opportunity to produce diesel with high yield and with high cetane number. Thus, in wet hydrocracking of a long-chain paraffin (n-hexadecane (n-C16)) over MFI nano-sheets, it was investigated whether catalytic activity increased with increasing number of Brønsted acid (H + ) sites (decreasing silicon-to-aluminium (Si/Al) ratio), while secondary cracking remained completely suppressed. Also, it was investigated whether more Al atoms could be incorporated into the framework of MFI nano-sheets by modifying the new synthesis method. It was demonstrated that the new synthesis method, which utilizes C22H45–N + (CH3)2–C6H12–N + (CH3)2–C6H13 (C22-6-6) as structure-directing agent (SDA), could be extended to various Si/Al ratios in the range 25 – 100. The nano-sheets exhibited extra-framework Al (EFAl) species. Nano-sheets with Si/Al = 75 exhibited an oddly large amount of EFAl species compared to the other nano-sheets. For nano-sheets with Si/Al = 75, a high fraction of the EFAl species may have formed during calcination of the ammonium form and may encompass flexible Al species with predominantly Al in octahedral coordination (AlVI). Nano-sheets were loaded with 0.9 wt% platinum (Pt) via incipient wetness impregnation (IWI). Pt/nano-sheets with Si/Al = 25, 50 and 100 exhibited similar and high Pt dispersion (γPt). In contrast, Pt/nano-sheets with Si/Al = 75 exhibited a very low γPt, which was probably a result of the abundance, nature and/or location of EFAl species present in the support. In dry hydrocracking of n-C16, the catalytic activity increased with decreasing Si/Al ratio, strongly suggesting that the number of H+ sites increased with decreasing Si/Al ratio. Nano-sheets with Si/Al = 75 most likely contained AlVI species associated with Brønsted acidity, supporting the presence of flexible AlVI species. In wet hydrocracking of n-C16, at a constant and sufficiently high γPt, the activity increased with increasing number of H+ sites (decreasing Si/Al ratio), while secondary cracking remained completely suppressed. Pt/nano-sheets with Si/Al = 75 displayed a lower activity than 2 Pt/nano-sheets with Si/Al = 100, which may be a result of the very low γPt of Pt/nano-sheets with Si/Al = 75, underlining the importance of high γPt. For Pt/nano-sheets with Si/Al = 25, 50 and 100, H2O favoured linear cracking products at low cracking yields. In contrast, for Pt/nano-sheets with Si/Al = 75, H2O favoured branched cracking products, which may be a result of Pt sites on the external surface of the support being too far from the H+ sites inside the micropores. The new synthesis method could be extended to a modified SDA, namely C22H45–N + (CH3)2–C6H12–N + (CH3)2–C3H7 (C22-6-3), at various Si/Al ratios in the range 25 – 100. Replacing the terminal –C6H13 group in C22-6-6 with –C3H7 resulted in an increase in the framework Al (FAl) content of MFI nano-sheets with Si/Al ≥ 50, with the increase being the most pronounced for nano-sheets with Si/Al = 50. This was due to the increased occupancy of the zeolite framework by the hydrophilic region of C22-6-3 in comparison to the hydrophilic region of C22-6-6 under the given set of synthesis conditions, since –C3H7 was less bulky than –C6H13. Calcined nano-sheets were loaded with 1 wt% Pt via competitive ion exchange (CIE). In dry and wet hydrocracking of n-C16, the activity increased with decreasing Si/Al ratio and in wet hydrocracking, secondary cracking was not completely suppressed up to high conversions. This was probably due to the presence of additional H+ sites generated after SDA removal. H2O favoured linear cracking products at low cracking yields. Sodium (Na+ ) ion-exchanged nano-sheets were loaded with 1 wt% Pt via CIE. The average Pt size (dPt) of the Pt/Na+ nano-sheets were larger than the dPt of the Pt/calcined nano-sheets, which may be a result of the nature and/or location of EFAl species present in the Na+ supports. In dry and wet hydrocracking of n-C16, differences in activity were observed and in wet hydrocracking, secondary cracking was not completely suppressed up to high conversions. This was probably due to insufficient intimacy between H+ sites and Pt sites such that the rate was controlled by diffusion of olefinic intermediates from H+ sites to Pt sites and vice versa. H2O favoured linear cracking products at low cracking yields.